Decentralized coordinated charging of electric vehicles considering locational and temporal flexibility. (1st September 2014) - D'hulst, Reinhilde; De Ridder, Fjo; Claessens, Bert; Knapen, Luk; Janssens, Davy
Summary: A method to coordinate the charging of electric vehicles to avoid network congestion issues is proposed. The novelty is that the proposed method uses both the temporal as well as the locational flexibility of the electric vehicles for coordination. Based on the vehicle behavior information (trajectories, parking places and duration, etc…), the algorithm assures that all vehicles can follow their planned trajectories and that power constraints on each car park are always met. The proposed method, a price‐based coordination method, is ran in a decentralized way. As a consequence the responsibility for constructing the charging schedules is put solely with the vehicle owners, and the charging location managers need only to be concerned with the network congestion issues. Simulation results for 1000 EV's and 132 parking locations are presented and discussed. Copyright © 2014 John Wiley & Sons, Ltd.